Linking Words with the World: The Language Poetry Mission - Koirala, Saroj (Tribhuvan University Journal, 2016)
The poets associated with the L=A=N=G=U=A=G=E School have remarkably borrowed from the Pound-Olson tradition of political poetry and poetics. But, they have also experimented with newer methods and matters that deviate from the tradition. Such continuation and departure from the tradition of the socio-cultural oriented language poets has been investigated here. Their poetic tenets have been examined through the ideas formulated by the outstanding cultural critics; Adorno, Jameson, Bakhtin, Foucault, Lukács, and Benjamin. Based on the thorough examination it has been found out that besides many other socio-cultural demands the language poets want to connect the words of art the world people live. Such connection, as they perform, has been disturbed for long time.